A grounded theory study of the narrative behind Indian physiotherapists global migration. (18th January 2019) - Grafton, Kate; Gordon, Frances
Summary: It is estimated that an additional 6.4 million allied health professionals are required to address India's health challenges. Physiotherapy is amongst the largest of these professions. Over the last decade, thousands of Indian physiotherapists have sought to study and work overseas. In this study, 19 physiotherapists from across India were interviewed. Data were collected and analysed using construct+ivist grounded theory methods. The findings indicate that the Indian physiotherapy profession faces many political and clinical hierarchical challenges within the Indian healthcare infrastructure. The profession's education provision has developed, and the private clinical sector has grown, but there are significant disparities in quality and standards across the sector. The profession in India has variable autonomy, is not nationally regulated, is poorly paid, and the leadership has been divided. The political, educational, and clinical context in Indian physiotherapy impacts upon physiotherapists' ability to practise effectively to their professional satisfaction. Individual physiotherapists are frustrated by their workplace and travel overseas where they hear that the physiotherapy profession and practice is different. Whilst the disjunctures influencing these factors continue, and overseas physiotherapy practice is perceived as different and superior, Indian physiotherapists will continue to seek to migrate overseas, and facilitating their return will be challenging.